Features of the formation and development of electronic transactions in the Republic of Kazakhstan and foreign countries (Journal of actual problems of jurisprudence, 2020)
The article is devoted to the study of the process of introducing new information technologies intocivil law relations, which occupies a special place not only in society and the market of Kazakhstan, butthroughout the world. The article considers not only electronic transactions (contracts) concluded onthe Internet that allow you to engage in distance trading, but also the formation of the first prototypesof Internet transactions. In addition, the article presents the history of the adoption of normative legalacts on electronic transactions, as well as their legal features in the United States, EU countries and theRepublic of Kazakhstan.The purpose of this article is to analyze information technologies that led to the emergence ofelectronic transactions, dividing into stages the history of the formation of electronic transactions inKazakhstan and abroad, studying the history of the legal origin of the concept of electronic transactions. The methodological basis of the article is composed of general scientific and special methods ofcognition such as systemic, logical-legal, historical and concrete sociological.The practical significance of the article lies in the possibility of using conclusions and proposals toimprove legislation in the field of electronic commerce by comparing the history of electronic transactionsbetween countries. The research results can be used in a practical analysis of the concept of electronictransactions, in the process of studying and explaining the institution of transactions.The theoretical foundations, content and conclusions discussed in the article complement and developmany sections of civil law and contract law.Key words: electronic transaction, Internet resources, information technology, electronic document.